IFLA: From Turmoil to Turmoil: based on an interview with Hans-Peter Geh - Frances Laverne Carroll (Information Development, 1994)
Hans-Peter Geh, President of IFLA from 1985 to 1991, talks to Laverne Carroll about his time in office and his views on international librarianship.